Determination of time mitotic of guadua angustifolia var. Grandicaula (Family: Gramineae) from roots meristem (Revista de Investigaciones Universidad del Quindío, 2011)
The bamboo species G. angustifolia is the most abundant in the neotropics, with varieties such as G. angustifolia var. grandicaula which has a wide distribution, being of great importance for their economic, social, cultural and scientific value. Due to the importance of this species, a technique was used to determine the mitotic hour in order to analyze their mitotic behavior for 24 hours. This was made from root meristems obtained from chusquines, which were hydrolyzed with 5N HCl and stained with 1% acetic orcein, finding that the highest peaks occur in the morning hours at 8:30 and afternoon  at 15:30 and 16:30; it is assumed that such behavior is related to the rate of metabolism these plants have.
Keywords: G. angustifolia var; grandicaula; mitotic hour; chusquin; root meristem